2007
DOI: 10.1183/09031936.00101706
|View full text |Cite
|
Sign up to set email alerts
|

The autoclavable semirigid thoracoscope: the way forward in pleural disease?

Abstract: Medical thoracoscopy is a valuable tool in the investigation and management of pleural disease. It has considerable advantages over conventional blind pleural biopsy and videoassisted thoracoscopic surgery. Despite this, the practice of this technique in the UK is limited. Most operators use the rigid thoracoscope, which may be an unfamiliar instrument to respiratory physicians. A semirigid thoracoscope is available but its use has not been possible in the UK as it requires sterilisation with ethylene oxide, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 14 publications
(15 reference statements)
8
68
2
3
Order By: Relevance
“…We used a flexi-rigid thoracoscope in this study, which has the advantage of being able to reach narrow spaces more easily with its bidirectional flexible tip that allows for pleural fluid aspiration and biopsy under visualization from a single port of entry. Flexirigid thoracoscopy is primarily performed to diagnose pleural effusions of unknown cause (11)(12)(13). Previously, we described the use of thoracoscopic talc poudrage under flexirigid thoracoscopy with one port of entry and a dedicated catheter (14).…”
Section: Discussionmentioning
confidence: 99%
“…We used a flexi-rigid thoracoscope in this study, which has the advantage of being able to reach narrow spaces more easily with its bidirectional flexible tip that allows for pleural fluid aspiration and biopsy under visualization from a single port of entry. Flexirigid thoracoscopy is primarily performed to diagnose pleural effusions of unknown cause (11)(12)(13). Previously, we described the use of thoracoscopic talc poudrage under flexirigid thoracoscopy with one port of entry and a dedicated catheter (14).…”
Section: Discussionmentioning
confidence: 99%
“…Alınan biyopsi parçalarının küçüklüğü nedeniyle tanı oranının düşebilecek olması da diğer bir sınırlayıcı durum olabilir. Ancak Munavvar ve arkadaşlarının 56 olguluk serisinde %90.7 tanıya ulaşılmıştır (11). Bizim dört olguluk serimizde tanı oranımız %75'tir.…”
Section: Discussionunclassified
“…This combination ensures flexibility for better inspection of the pleural cavity and, at the same time, improves biopsy sampling with the rigid part. The diagnostic accuracy of flex-rigid thoracoscopes in cases of undiagnosed pleural effusion is the same as for rigid devices (on average 93%) (8,9). Although a recent study showed equal results in diagnostic accuracy with a rigid device, further large comparative studies are needed to confirm the results (1).…”
Section: Development Of New Devicesmentioning
confidence: 94%